Implementation of Agrarian Reform in Realizing People's Justice and Welfare (Case Study at BPN Deli Serdang Regency) - Nabilah Syaharani; Dahlan Dahlan; Abdul Razak Nasution (CV. Era Digital Nusantara, 2026)
This study aims to analyze the implementation of Agrarian Reform by The National Land Agency (BPN) of Deli Serdang Regency in the 2020–2025 period and identify the main obstacles faced and efforts to solve them. This research uses a type of qualitative research with the nature of empirical juridical research, namely examining the legal provisions that govern Agrarian Reform and relating it to implementation practices in the field. The research data was obtained through in-depth interviews with officials and apparatus of the Deli Serdang Regency BPN, documentation studies, and tracing of relevant laws and regulations. The results of the study show that the implementation of Agrarian Reform in Deli Serdang Regency has been carried out systematically and guided by the national regulatory framework, especially the Basic Agrarian Law and Presidential Regulation Number 62 of 2023 concerning the Acceleration of the Implementation of Agrarian Reform. The implementation of Agrarian Reform is realized through asset legalization, land redistribution, and access arrangement that is integrated with the Complete Systematic Land Registration (PTSL) program and coordinated through the Agrarian Reform Task Force. The main obstacles faced include low community participation in several locations as well as the complexity of physical and juridical data that has the potential to cause land disputes. Efforts to resolve it are carried out through strengthening cross-sector coordination, increasing socialization to the community, and applying the principle of prudence by ensuring that the objects and subjects of Agrarian Reform are in a clean and clear condition. This research is expected to make an academic and practical contribution to the development of more effective and equitable Agrarian Reform policies.